Assessment of Functional Outcome of Bicolumnar Dual Plating for Bicondylar Fractures of Tibial Plateau - Shrestha, Dinesh Kumar; KC, Dipendra; Karki, Prateek; Shrestha, Sabin; Yogi, Sushil (Journal of Nepalgunj Medical College, 2022)
Introduction: Operative treatment of bicondylar fractures of tibial plateau is challenging and controversial.Aims: The aim of this study is to reveal the functional outcome of it by using bicolumnar dual plates and screws.Methods: This is a prospective hospital based interventional study carried out in the department of Orthopaedics of Nepalgunj Medical College Teaching Hospital. Thirty two Schatzker type V or AO (Association of Osteosynthesis) type 41 C1 & C2 fractures were treated between January 2016 and December 2019 with bicolumnar dual plating. The functional clinical outcomes were analyzed and evaluated using modified Rasmussen score.Results: Thirty two patients were included in the study. Out of which twenty four were male and eight were female. Average age was 32.21 years, eighteen were right sided and fourteen were left sided. Duration of surgery was 106 mins (range 90-120 mins) and the average duration of hospitalization was 7.81 days (range 4-14 days). Five patients of impending compartment syndrome and three patients with common peroneal nerve palsy were managed conservatively and also were included in the study. Two patients with superficial wound infection needed minimal debridement. One patient had varus angulation of 100 at third follow up after he fell from bed but surgical intervention were not needed. All fractures united. The average time for fracture healing was 21.5 weeks (range 16-32 weeks). At the Eighteen months follow up, the average knee range of motion was 1310(range 1100-1400). The functional outcome were evaluated using modified Rasmussen scoring system, which was 27.34 (range 22-30).Conclusion: Bicolumnar dual plating for bicondylar fractures of tibial plateau can provide excellent and stable fixation allowing early range of motion and gives excellent to good functional outcome.